2004
DOI: 10.1177/154405910408301213
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Oral-health-related Quality of Life

Abstract: Oral-health-related quality of life (OHRQoL) is expected to have multiple dimensions. It was the aim of this study to investigate the dimensional structure of OHRQoL measured by the Oral Health Impact Profile (German version) (OHIP-G) and to derive a summary score for the instrument. Subjects (N = 2050; age, 16-79 yrs) came from a national survey. We used rotated principal-components analysis to derive a summary score and to explore the dimensional structure of OHIP-G. The first principal component explained 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
142
1
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 14 publications
12
142
1
14
Order By: Relevance
“…OHIP-14 consists of 14 items organized into 7 theoretical fields (functional limitation, pain, psychological discomfort, physical disability, psychological disability, social disability and handicap) (32). The OHIP-14 instrument is useful for quantifying levels of impact on well-being in a setting where only a limited number of questions can be used.…”
Section: Questionnairementioning
confidence: 99%
“…OHIP-14 consists of 14 items organized into 7 theoretical fields (functional limitation, pain, psychological discomfort, physical disability, psychological disability, social disability and handicap) (32). The OHIP-14 instrument is useful for quantifying levels of impact on well-being in a setting where only a limited number of questions can be used.…”
Section: Questionnairementioning
confidence: 99%
“…Studies have demonstrated the impact of oral health conditions on physical and psychosocial dimensions (John et al, 2004;Locker & Allen, 2007;Settineri, Rizzo, Liotta, & Mento, 2014), while there is a lack of scientific evidence about the link between OHRQoL and emotions. The majority of existing studies have focused exclusively on the relationship with dental anxiety (Kurer, Watts, Weinman, & Gower, 1995;McGrath & Bedi, 2004) and/or depression (MarquesVidal & Milagre, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the questionnaires designed for this purpose relate to the number of questions, the question content, the answer format, the grouping of topics in different domains, and the number of domains. 32 Most studies that investigate the subjective perception of edentulous patients before and after IMO rehabilitation evaluate OHRQoL based on one questionnaire (e.g., DIDL, GOHAI, or OHIP-EDENT). Consequently, the limitations and differences in sensitivity across various domains of each questionnaire with respect to the others remain unknown.…”
Section: Discussionmentioning
confidence: 99%